2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5332822
|View full text |Cite
|
Sign up to set email alerts
|

Neural prosthetic systems: Current problems and future directions

Abstract: Abstract-By decoding neural activity into useful behavioral commands, neural prosthetic systems seek to improve the lives of severely disabled human patients. Motor decoding algorithms, which map neural spiking data to control parameters of a device such as a prosthetic arm, have received particular attention in the literature. Here, we highlight several outstanding problems that exist in most current approaches to decode algorithm design. These include two problems that we argue will unlikely result in furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 50 publications
3
35
1
Order By: Relevance
“…Because previous studies have indicated that multi-unit recordings can provide decoding of direction equivalent to that of single-units (Liu and Newsome, 2006; Chestek et al, 2009), in the present analysis we treated single-unit and multi-unit spike recordings equivalently. Figure 6 illustrates spike recordings from two single units recorded in session Y0225, one from array H (2.0 mm deep to the hemispheric surface) and one from array I (1.5 mm deep).…”
Section: Resultsmentioning
confidence: 99%
“…Because previous studies have indicated that multi-unit recordings can provide decoding of direction equivalent to that of single-units (Liu and Newsome, 2006; Chestek et al, 2009), in the present analysis we treated single-unit and multi-unit spike recordings equivalently. Figure 6 illustrates spike recordings from two single units recorded in session Y0225, one from array H (2.0 mm deep to the hemispheric surface) and one from array I (1.5 mm deep).…”
Section: Resultsmentioning
confidence: 99%
“…A 96-channel silicon electrode array (Blackrock Microsystems, Salt Lake City, UT) was implanted in motor cortex contralateral to the reaching arm. When identifying neural spikes on each electrode, threshold crossings (Chestek et al, 2009; Fraser et al, 2009) were used in place of spike sorting. For monkey L, we also required voltage waveforms to pass a shape heuristic.…”
Section: Methodsmentioning
confidence: 99%
“…Spikes may be stable only across days to weeks, and even then only for a subset of channels (Chestek et al 2009;Dickey et al 2009), necessitating the frequent updating of decoding filters (Hochberg et al 2006). On an array where the number of spiking units is small or decreases over time, LF, H1, and H2 signals may provide a substitute signal to create a robust decoder.…”
Section: Implications For Bci Applicationsmentioning
confidence: 98%
“…Thus comparisons with MUA-based decoding require a careful analysis of the actual signal employed. The relative performance of decoders based on sorted (our SA signal) or thresholded but unsorted spikes (Chestek et al 2009) is a subject of ongoing research for BCI applications.…”
Section: Nature Of Signalsmentioning
confidence: 99%